WALCOM: algorithms and computation 5th international workshop, WALCOM 2011, New Delhi, India, February 18-20, 2011: proceedings - WALCOM (Workshop) New Delhi, India) 2011; Katoh, Naoki; Kumar, Amit.; SpringerLink (Online service). (Berlin New York Springer, 2011)
This book constitutes the proceedings of the 5th International Workshop on Algorithms and Computation, WALCOM 2011, held in New Delhi, India, in February 2011. The 20 papers presented in this volume were carefully reviewed and selected from 57 submissions.  The papers are grouped in topical sections on approximation algorithms, hardness, algorithm engineering, computational geometry, string algorithms, and graph algorithms.
Electronic reproduction.
Keywords: Computer algorithms -- Congresses; Electronic books